PENGASUHAN ORANG TUA DAN KEMANDIRIAN ANAK USIA 3-5 TAHUN BERDASARKAN GENDER DI KAMPUNG ADAT URUG - Dewanggi, Mustika; Hastuti, Dwi; Hernawati, Neti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2012)
This study aimed to analyze correlation between child and family characteristics with caring practices and children’s autonomy, and also analyzed difference of caring practices and children’s autonomy based on gender at Kampung Adat Urug, Kiarapandak Village, Sukajaya District, Bogor Regency. This research involved 60 families with 3 to 5 years old childrens that choosed by using proportional random sampling method. The data was collected by observations and interview using questionnaire research. Data was analyzed using Pearson correlation test, Chi-square test, and different t-test. The result showed that parenting practices that measured by food caring practices and healthy life caring practices differ significantly by gender. The study also revealed that there was relationship between caring practices and children’s autonomy. The children’s autonomy was related with children’s age and family income. The better the parenting the better the children’s autonomy.